Influence of the carbonization atmosphere on the development of highly microporous adsorbents tailored to CO2 capture. (June 2022) - Gomez-Delgado, Edward; Nunell, Gisel V.; Cukierman, Ana Lea; Bonelli, Pablo R.
Abstract: Two microporous activated carbons (ACs) tailored to CO2 capture were developed from Prosopis ruscifolia sawdust. The ACs were obtained through a two-stage process. The first consisted in the carbonization of the precursor, while the second involved chemical activation employing KOH solution as activating agent. The influence of the atmosphere involved in the carbonization stage (N2 flow at 773 K or air flow at 573 K) on the chemical and textural-morphological characteristics of the resulting ACs and on their CO2 removal capacity was analyzed. The ACs presented similar properties with a predominance of microporous structures, BET surface areas slightly larger than 1000 m 2  g −1, and micropore volumes of ∼0.43 cm 3  g −1 on average. Both ACs also showed a predominance of surface acidic functionalities over basic ones. The adsorbed amounts of CO2 as determined from the isotherms were 5.6 and 5.3 cm 3  g −1, for the ACs developed from the precursor carbonized under N2 and air flow, respectively. From thermogravimetric tests to assess adsorption kinetics, values of the CO2 removal (101.325 kPa and 303 K) reached at equilibrium conditions were 1.15 and 1.04 mmol g −1, respectively. Present results demonstrated that the carbonization atmosphere did not have a pronounced effect on chemical and textural characteristics of the resulting ACs and, consequently, on their CO2 adsorption capacity. Accordingly, the use of air instead of N2 in the carbonization stage of the activation process may represent an interesting alternative because of the lower operating temperature involved, leading to reduce energy consumption and operating costs without sensibly affecting ACs performance. Highlights: Activation of biochar obtained under air or N2 flow led to nanoporous carbons. Adsorbents features were similar regardless the biochar employed. Carbonization in air flow saves energy and N2 consumption.